Toxicidade aguda e efeitos analgésico e depressor do extrato aquoso obtido das folhas de Pluchea sagittalis (Lam.) Cabrera (quitoco) - Rodrigues, Sheyla Alves (2007)
The Pluchea sagittalis (Lam) Cabreira, Family Asteraceae, is a plant of the Atlantic Reainforest used in traditional medicine for the treatment of inflammation, as well as of digestive and respiratory diseases. The objective of this dissertation work was to study the possible effects of the aqueous extract of Pluchea sagittalis (Lam) Cabreira, on the Central Nervous System and acute toxicity in mice. This plant is used in traditional medicine for the treatment of inflammation, as well as of digestive and respiratory diseases. The Acute Toxicity (DL50) was gotten by the administration of the doses 1000, 2000 and 3000 mg/Kg, in according to legislation by National Agency of Sanitary Vigilance (ANVISA), but not being observed toxic effect. The possibilities of pharmacological actions had been analyzed by the test of screening pharmacological that showed the possible action of the extract as depress of the CNS. The antinociceptive effect was evaluated by using two models: acetic acid induced writhing and Tail-Flick test. In the first one was showed the analgesic effect of the extract with values of p > 0,01 in the dose of 200mg/Kg and p < 0,001 in the dose of 100 and 400 mg/Kg, when compared with the control group. The Tail-Flick test confirmed the analgesic effect of the extract with values of p<0,001, for all the doses, in the time of 30 and 60 minutes, with detach it 120 minutes after dose of 400 mg/Kg that kept p<0,001. On the sleep-induced by thiopental the extract was showed significance with p<0,05 at the return of the righting reflex and p<0,001, in the total time of sleep, for all the doses, with detach for the dose of 400 mg/Kg that showed the best effect. Thus the tests acetic acid induced writhing, Tail-Flick and sleep-induced by thiopental come to confirm the effect depress of this plant on the central nervous system initially identified for the screening pharmacological e for the traditional medicine.